Increasing a sense of Responsibility Through Cooking Classes for 4-5 year olds at Sidoarjo Kindergarten: Peningkatan Rasa Tanggung Jawab Melalui Kegiatan Cooking Class Pada Anak Usia 4-5 Tahun di Taman Kanak-Kanak Sidoarjo - Dewi, Fitria; Salim, Agus (Indonesian Journal of Education Methods Development, 2022)
This research was conducted to increase children's sense of responsibility with cooking class activities for Group A children at the Dharma Wanita Persatuan Sedenganmijen Krian Kindergarten. Aspects of responsibility examined include: 1) children take care of public property, 2) children tidy up equipment/toys after use, 3) children carry out tasks that have been given by the teacher. This research method is included in classroom action research. This research was conducted in three cycles. The subjects of this study were Group A children with 15 children consisting of 5 boys and 10 girls. How to collect data by observation, interviews, and documentation. In the results of this study, it can be seen that there is an increase in children's sense of responsibility in the 3 cycles that have been carried out. Children's sense of responsibility has increased with cooking class activities because there are rules that must be followed and work to completion. So that it makes children more responsible which includes maintaining public property, tidying up equipment/toys after use and carrying out tasks that have been given by the teacher.